2017
DOI: 10.1503/jpn.160010
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging of the putamen in patients with major depressive disorder

Abstract: IntroductionMajor depressive disorder (MDD) is primarily characterized by depressed mood and a blunted experience of pleasure (i.e., anhedonia). 1 The disorder is prevalent and chronic and represents a substantial personal, social and economic burden. [2][3][4] Neuroscience promises to elucidate mechanisms under lying depressive pathophysiology, leading to more effective approaches to the prevention and treatment of this debilitating disorder.Considerable evidence indicates that reward processing is dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
35
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 48 publications
11
35
3
Order By: Relevance
“…We speculate that depression may interact with the normal aging process, as results of diagnosis-by-age interaction analysis showed that MDD is associated with increased decline in overall and interhemispheric FA with age. These results suggest that MDD may be associated with accelerated brain aging, which has been shown for regional gray matter volume [44,45], although longitudinal studies are required to confirm this hypothesis. A previous study did not observe a diagnosisby-age interaction effect on WM, but this study was performed in a smaller sample of patients and controls and may have been underpowered to detect small effects [46].…”
Section: Discussionsupporting
confidence: 52%
“…We speculate that depression may interact with the normal aging process, as results of diagnosis-by-age interaction analysis showed that MDD is associated with increased decline in overall and interhemispheric FA with age. These results suggest that MDD may be associated with accelerated brain aging, which has been shown for regional gray matter volume [44,45], although longitudinal studies are required to confirm this hypothesis. A previous study did not observe a diagnosisby-age interaction effect on WM, but this study was performed in a smaller sample of patients and controls and may have been underpowered to detect small effects [46].…”
Section: Discussionsupporting
confidence: 52%
“…The marked variation in ν and D L may be related to the reduced volume of the CP in the anhedonic group, an effect that is thought to be implicated in cognitive and motor abnormalities . In the same vein, clinical studies have also shown a significant reduction in the volume of CP in patients with depressive disorders . However, we did not observe any volumetric alterations in the CP either.…”
Section: Discussioncontrasting
confidence: 63%
“…7 In the same vein, clinical studies have also shown a significant reduction in the volume of CP in patients with depressive disorders. 56 However, we did not observe any volumetric alterations in the CP either. Delgado y Palacios et al have reported a significantly higher volume of CP in a similar animal model of depression after eight weeks of CMS exposure.…”
Section: Figurecontrasting
confidence: 61%
“…On one hand, the abnormal deposition of iron might be the result of the depression. Many fMRI studies have suggested that the basal nuclei displayed structural transformation as well as dysfunction in depression (Sacchet et al, 2017 ; Zhao et al, 2017 ). More and more evidence suggests that these changes to the basal nuclei, which are associated with motor function, and associative and limbic circuits, were related to the destruction of the dopaminergic system (Schroll and Hamker, 2016 ; Markett et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%